Discovery of the local counterpart of disc galaxies at z > 4: the oldest thin disc of the Milky Way using Gaia-RVS - Nepal, Samir; Chiappini, C.; Queiroz, A. B.; Guiglion, Guillaume; Montalbán, J.; Steinmetz, M.; Miglio, A.; Khalatyan, A. (Astronomy and astrophysics, 2024)
Context. JWST recently detected numerous disc galaxies at high redshifts, and there have been observations of cold disc galaxies at z > 4 with ALMA. In the Milky Way (MW), recent studies highlight the presence of metal-poor stars in cold-disc orbits, suggesting an ancient disc. This prompts two fundamental questions. The first refers to the time of formation of the MW disc, and the second to whether it originated as the thin disc or the larger velocity dispersion thick disc. Aims. We carried out a chrono-chemo-dynamical study of a large sample of stars with precise stellar parameters, focusing on the oldest stars in order to decipher the assembly history of the MW discs. Methods. We investigated a sample of 565 606 stars with 6D phase space information and high-quality stellar parameters coming from the hybrid-CNN analysis of the Gaia-DR3 RVS stars. The sample contains 8500 stars with [Fe/H] < −1. For a subset of ∼200 000 main sequence turn-off (MSTO) and subgiant branch (SGB) stars, we computed distances and ages using the StarHorse code, with a mean precision of 1% and 12%, respectively. Results. First, we confirm the existence of metal-poor stars in thin-disc orbits. The majority of these stars are predominantly old (> 10 Gyr), with over 50% being older than 13 Gyr. Second, we report the discovery of the oldest thin disc of the Milky Way, which extends across a wide range of metallicities, from metal-poor to super-solar stars. The metal-poor stars in disc orbits manifest as a readily visible tail of the metallicity distribution. We calculate the vertical velocity dispersion (σVz) for the high-[α/Fe] thick disc, finding 35 ± 0.6 km s−1, while the thin disc within the same age range has a σVz that is lower by 10-15 km s−1. Our old thin disc σVz appears similar to those estimated for the high-z disc galaxies. Third, as a verification of StarHorse ages, we extend the [Y/Mg] chemical clock to the oldest ages and estimate a slope of −0.038 dex ⋅ Gyr−1. Finally, we confirm our discovery of the old thin disc by showing that the ‘splash’ population includes high- and low-[α/Fe] populations that are both old, and extends to a wider [Fe/H] range, reaching supersolar [Fe/H]. We find that about 6-10% of the old thin disc was heated to thick-disc orbits. The youngest ‘splashed’ stars appear at 9-10 Gyr and may suggest a Gaia-Sausage/Enceladus (GSE) merger at this period. Conclusions. The Milky Way thin disc formed less than 1 billion years after the Big Bang and continuously built up in an inside-out manner - this finding precedes the earlier estimates of the time at which the MW thin disc began to form (around 8-9 Gyr) by about 4-5 billion years. We find that the metal-poor stars in disc orbits reported by previous studies belong to this old thin disc. Considering a massive merger event such as the GSE, a splash is expected - we find a portion of the old thin disc is heated to thick disc velocities and the splash extends to supersolar [Fe/H] regimes.
Online veröffentlicht: 15. August 2024
Gesehen am 05.09.2025